ANALISIS LOGAM BERAT (Mn, Fe , Cd), SIANIDA DAN NITRIT PADA AIR ASAM TAMBANG BATU BARA - Kiswanto, Kiswanto; Wintah, Wintah; Rahayu, Nur Laila (BAPPEDA Kota Pekalongan, 2020)
Coal mining of PT. Mifa Brothers in Aceh Barat produces liquid waste containing hazardous heavy metals. Research conducted at PT. Mifa Brothers located in Sumber Batu Village, Meureubo Subdistrict, West Aceh Regency, Aceh Province. The coal mining activities by the PT. Mifa Brothers used open-cast mining systems with open method. From the resulting liquid waste, the PT. Mifa Brothers made two ponds used as liquid waste treatment. Efficiency of Sewage Treatment Plant (STP or IPAL) conducted by the industry, can be known through the analysis of he avy metals content (Fe, Mn and Cd), cyanide and nitrite on inlet and outlet of liquid waste shelter. This analysis was determined using the atomic absorption Spectropotemer (SSA) for metal Fe, Mn and Cd, while CN-and NO2-analysis-using UV-Vis spectrophotometry methods. Test result of heavy metal ions of iron ion, manganese ions, cadmium ions, nitrite, and cyanide on each inlet is 8.24; 0.223; < 0.01; 0.034 mg/L and 0.321 on each outlet are 3.03; 0.189; < 0.01 mg/L; 0,016 and undetectable for cyanide. Sewage treatment at PT. Mifa Brothers using Dolomite method as adsorbent has not been efficient and efficient in the reduction of pollutant levels. Keywords : SSA, UV-Vis spectrophotometry, Inlet and outlet, Fe, Mn, Cd,NO2, CN-